The effect Mat Pilates practice on muscle mass in elderly women - Queiroz, Leliz Cristina Sampaio; Bertolini, Sonia Maria Marques Gomes; Bennemann, Rose Mari; Silva, Eraldo Schunk (Rev Rene, 2016)
Objective: to verify that the Mat Pilates practice increases muscle mass in elderly women. Methods: quasiexperimental study with primary data collection and with a convenience sample. The muscle mass of 43 elderly was evaluated for 11 weeks, by calculating the arm muscle area, before and after the intervention. Results: statistically significant difference was observed (p